Acerca del Codex Calixtinus: Rozas (4.3) - Martínez Ortega, Ricardo (2001)
Acaba de aparecer un voluminoso estudio sobre la dificilísima toponimia del Liber Sancti Jacobi, debido a J. M.a Anguita Jaén. La identificación de “Rozas” (4,3) con Rosas (Gerona, España) es rechazada por el autor de este artículo mediante el estudio intrínseco y la comparación extrínseca. Propone la identificación con la antigua sede episcopal de Roda de Isábena (Huesca, España).
A voluminous study about the difficult toponymy in Liber Sancti Jacobi, due to J. M.a Anguita Jaén, has just appeared. The identification of “Rozas” (4,3) with Rosas (Gerona, Spain) has been rejected by the author of this article through an intrinsic study and an extrinsic comparison. It has been suggested the identification with the old Episcopal See of Roda de Isábena (Huesca, Spain).
Keywords: Pseudo Turpin; Liber Sancti Jacobi; Toponimia; Camino de Santiago